Lipidomic Alterations in the Mitochondria of Aged Parkin Null Mice Relevant to Autophagy - Gaudioso, Angel; Garcia-Rozas, Patricia; Casarejos, Maria Jose; Pastor, Oscar; Rodriguez-Navarro, Jose Antonio (Frontiers in Neuroscience, 2019)
Mitochondrial quality control is important in neurological diseases, but in the genetic Parkinson´s disease caused by mutations in PINK and parkin mitochondrial degradation through autophagy is crucial.. Reductions in autophagy and mitophagy are implicated in aging, age related diseases and Parkinson. The parkin null mice (PK-KO) show only a subtle phenotype, apparent with age or with stressors. We have studied the changes in the lipidomic composition of the mitochondrial membranes isolated from the brains of young and old PK-KO mice and compared them to wild type in order to determine possible implications for Parkinson´s disease pathology. We observed an increase in the levels of phosphatidylethanolamine in the young PK-KO mice that is lost in the old and correlate to changes in the phosphatidylserine decarboxylase. PK-KO old mice mitochondria showed lower phosphatidylglicerol and phosphatidylinositol levels and higher levels of some forms of hydroxylated ceramides. Regarding cardiolipins there were changes in the degree of saturation mainly with age. The lipidomic composition discriminates between the study groups using partial least square discriminant analysis. We discuss the relevance of the lipid changes for the autophagic activity, the mitophagy, the mitochondrial activity and the Parkinson´s disease pathology in absence of parkin.